Polar Cation Ordering: A Route to Introducing >10% Bond Strain Into Layered Oxide Films. (5th September 2014) - Nelson‐Cheeseman, Brittany B.; Zhou, Hua; Balachandran, Prasanna V.; Fabbris, Gilberto; Hoffman, Jason; Haskel, Daniel; Rondinelli, James M.; Bhattacharya, Anand
<x xml:space="preserve">Abstract</x> The 3d transition metal (M) perovskite oxides exhibit a remarkable array of properties, including novel forms of superconductivity, magnetism and multiferroicity. Strain can have a profound effect on many of these properties. This is due to the localized nature of the M 3d orbitals, where even small changes in the M–O bond lengths and M–O–M bond angles produced by strain can be used to tune the 3d– O 2p hybridization, creating large changes in electronic structure. A new route is presented to strain the M–O bonds in epitaxial two‐dimensional perovskite films by tailoring local electrostatic dipolar interactions within every formula unit via atomic layer‐by‐layer synthesis. The response of the O anions to the resulting dipole electric fields distorts the M–O bonds by more than 10%, without changing substrate strain or chemical composition. This distortion is largest for the apical oxygen atoms (Oap), and alters the transition metal valence state via self‐doping without chemical substitution.